2006
DOI: 10.2337/diabetes.55.03.06.db05-1143
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Regulation of Proopiomelanocortin Neurons by Leptin in the Nucleus of the Solitary Tract and in the Arcuate Hypothalamic Nucleus

Abstract: (4,5). POMC neurons produce several neuropeptides derived from the POMC-polypeptide precursor, including the melanocortins ␣-, ␤-, and ␥-melanocyte-stimulating hormone (MSH), which are ligands for the melanocortin-3 and -4 receptors (MC3/4R) (6,7). A separate population of leptin-responsive cells in the ARC is the agouti-related peptide-producing (AgRP) neurons, which coexpress neuropeptide Y. AgRP is an antagonist of the melanocortin peptides at the MC3/4R (8). In contrast to POMC neurons, AgRP/neuropeptide Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
91
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 59 publications
9
91
3
Order By: Relevance
“…Our data indicate that fasting alters the biosynthesis of POMCderived peptides in the NTS, although biosynthesis is not directly regulated by leptin. Recently, it was shown that fasting-induced reduction of pomc mRNA in the in the NTS was not reversed by leptin (26). These findings support our transcription data.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our data indicate that fasting alters the biosynthesis of POMCderived peptides in the NTS, although biosynthesis is not directly regulated by leptin. Recently, it was shown that fasting-induced reduction of pomc mRNA in the in the NTS was not reversed by leptin (26). These findings support our transcription data.…”
Section: Discussionsupporting
confidence: 83%
“…However, our results strongly indicate that this effect of leptin is not mediated by POMC-related peptides produced in the NTS. Different from our study and Huo et al (26), another laboratory suggested that peripheral administration of leptin induced pSTAT3 activation in about 30% of the POMC-EGFP neurons in the NTS (12). Although the phosphorylation of STAT3 is valid and widely used to indicate leptin signaling, pSTAT3 could participate in other signaling pathways independent of the biosynthesis of POMC.…”
Section: Discussioncontrasting
confidence: 51%
“…Common neuronal populations in the NTS. NPY-and POMC-expressing cells are present in the NTS, and colocalization of POMC with GFP expression here has been confirmed in POMC-GFP mice (14). We confirmed the colocalization of NPY with GFP expression in the NTS of NPY-GFP mice.…”
Section: Neuronal Populations In Outflow Tracts Common To Liver and Asupporting
confidence: 74%
“…Neurons in several feeding-relevant caudal brain stem nuclei, including the nucleus of the solitary tract (NTS, an area thought to be involved in satiety), express the long (signaling) form of the leptin receptor (7,13). Peripheral injection of leptin induces phosphorylation of STAT3 (pSTAT3, a marker of leptin receptor activation) in NTS cells (9,10), as well as in hypothalamic populations, adding strength to the suggestion that leptin acts directly on hindbrain sites. Furthermore, leptin injected into the dorsal vagal complex (DVC, which contains the NTS, area postrema, and dorsal motor nucleus of the vagus nerve) reduces food intake and body weight at doses that are subthreshold for such effects following ventricular administration (7).…”
mentioning
confidence: 99%